2019
DOI: 10.1111/cid.12842
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of resonance frequency analysis devices to evaluate implant stability of narrow diameter implants at varying drilling speeds in dense artificial bone blocks

Abstract: Background There are no studies that have assessed the implant stability quotient (ISQ) values of narrow diameter implants placed in artificial dense bone blocks at varying drilling speeds (DSs). Purpose The aim of the present in vitro experiment was to compare the performance of OSSTELL and Penguin devices to evaluate implant stability at DSs of 800 and 2000 rpm. Materials and Methods A total of 360 osteotomies were created in dense artificial bone blocks at DSs of 800 and 2000 rpm. Dental implants from three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Negative PTV values indicate the implant's stability for potential immediate load and positive higher values indicate implant micromovement and potential contraindication for implant loading [48]. The resonance frequency analysis has demonstrated reliability in in vitro studies, [49] and values over >60 ISQ allow immediate loading. However, variations in the tightening force of the transducer on the implant can increase the variability of the stability measurements [50].…”
Section: Discussionmentioning
confidence: 99%
“…Negative PTV values indicate the implant's stability for potential immediate load and positive higher values indicate implant micromovement and potential contraindication for implant loading [48]. The resonance frequency analysis has demonstrated reliability in in vitro studies, [49] and values over >60 ISQ allow immediate loading. However, variations in the tightening force of the transducer on the implant can increase the variability of the stability measurements [50].…”
Section: Discussionmentioning
confidence: 99%
“…The transducer peg for each device (smartpeg for Osstell and MegaISQ and multipeg for Penguin) was inserted on each implant according to the manufacturer's instructions, and two measurements were recorded parallel and perpendicular (lingual) to the longitudinal axis of the peg. Due to the reliability provided by previous studies [12][13][14][15], Penguin ® was used as the control.…”
Section: Methodsmentioning
confidence: 99%
“…These analyses have focused on two devices: Osstell ® (W&H, Göteborg, Sweden) and Penguin ® (Integration Diagnostics Sweden AB, Göteborg, Sweden) [12][13][14]. For instance, Buyukguclu et al [12] reported better reliability for Osstell ® , while Romanos et al [13] reported that both devices were sensitive and reliable. Bural et al reported excellent reliability for Penguin ® , but they did not report the reliability of Osstell ® [14].…”
Section: Introductionmentioning
confidence: 99%
“…After being excited, it vibrates and emits an electric voltage to the probe that will be transformed into an ISQ value. ISQ values seems to be influenced by several factors such as bone implant contact (BIC), which in turn is influenced by implant morphology and surface properties, among others; implant design, length, and diameter [ 4 ]; force at which the transducers are screwed (4–5 N/cm are recommended) [ 9 , 10 , 11 ]; interposed soft tissue between the SmartPeg and the implant [ 4 ]; bone quality [ 12 ]; probe position and effective implant length (EIL), which is defined as the distance from the transducer to the marginal bone (the greater the distance, the lower ISQ values are obtained) [ 4 , 10 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%